Globalization and its impact on tricycle drivers in the Philippine informal economy - Malit, Froilan T. Jr (Philippine Journal of Labor and Industrial Relations, 2010)
This paper is an inquiry on the impact of globalisation on the livelihood of unionised tricycle drivers in the rural Philippines. In particular, it analyses how the influx of motorcycles undermined the business of local tricycle drivers in Floridablanca, the third largest municipality in Pampanga. This paper examines the effects of these imported vehicles in the informal economy. The paper supports measures strengthening or providing social and labor protection for Filipino tricycle drivers in the Philippine informal economy.